Analisis Kriminologis Terhadap Pelaku Tindak Pidana Perdagangan Orang (Studi di Kepolisian Resort Sinjai) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine the factors responsible for a person who is a criminal act of trafficking in persons, to determine the preventive actions taken by law enforcement officials in this case, especially the Sinjai Resrot Police to tackle the crime of trafficking in persons. This type of research is a descriptive empirical legal research. Using a qualitative legal research approach. The location of the legal research was carried out at the Sinjai Police. Types and sources of legal research data including primary data and secondary data. Data interview techniques with interviews and literature study. Based on the results of the research and discussion, the conclusion is that the criminal act of trafficking in persons consists of economic factors, based on work, education and information, disharmony family conditions, consumptive culture, a woman, and mass media factors. Regarding efforts to tackle the criminal act of trafficking in persons, namely by means of law enforcement officials that have an impact on the perpetrators of the crime of trafficking in persons, socialization is needed, urging the public to be active in reporting matters suspected of being related to criminal acts, deepening religious teachings.AbstrakPenelitian ini bertujuan untuk mengetahui faktor-faktor penyebab seseorang melakukan tindak pidana perdagangan orang, untuk mengetahui upaya-upaya yang dilakukan oleh aparat penegak hukum dalam kasus ini khususnya pihak Kepolisian Resrot Sinjai untuk menanggulangi tindak pidana perdagangan orang. Jenis penelitian ini merupakan penelitian hukum empiris bersifat deskriptif. Menggunakan pendekatan penelitian hukum kualitatif. Lokasi penelitian hukum dilakukan di Polres Sinjai. Jenis dan sumber data penelitian hukum meliputi data primer dan data sekunder. Teknik pengumpulan data dengan wawancara dan studi kepustakaan. Berdasarkan hasil penelitian dan pembahasan dihasilkan simpulan bahwa faktor terjadinya tindak pidana perdagangan orang terdiri dari faktor ekonomi, kurangnya lapangan pekerjaan, kurangnya pendidikan dan informasi, keadaan keluarga yang tidak harmonis, budaya konsumtif, diskriminasi wanita, dan faktor media massa. Mengenai upaya-upaya untuk menanggulangi tindak pidana perdagangan orang yakni dengan cara aparat penegak hukum memberikan efek jerah bagi pelaku tindak pidana perdagangan orang, diperlukan adanya sosialisasi, mendrng masyarakat agar berpartisipasi aktif dalam melaporkan hal-hal yang dicurigai terkait dengan tindak pidana, pendalaman ajaran agama.